Mobility and fractionation of copper in sandy soils. Issue 1 (1st January 2019) - Sun, Qian; Li, Tiantian; Alva, A. K.; Li, Yuncong C.
ABSTRACT: The transport and fractionation of copper (Cu) were investigated in three soils which were under continuous citrus production for over 30 years. The above soils received 50 kg Cu ha −1, and were leached with eight pore volumes of water (equivalent to a total of 91 cm of rainfall). Following the completion of leaching, the leaching columns were sectioned into 5 cm depth increments for analyses of soil Cu. Concentrations of different forms of soil Cu were analyzed using a sequential fractionation procedure. The leaching column study indicated as much as 98% of the applied Cu remained in the upper 5 cm of the soil despite leaching eight pore volumes of water. Copper recovered in eight pore volumes of leachate accounted for 0.18–2.87% of Cu applied. The organically bound and precipitated forms of Cu accounted for 33–87% and 6–44% of total soil Cu, respectively.